Activated complex theory is a classical theory suitable for food science with appropriate use. (1st December 2020) - Zheng, Liyou; Jin, Jun; Karrar, Emad; Wang, Xingguo; Jin, Qingzhe
Highlights: There are some errors when applying ACT in food science mainly during 2014–2019. An elementary step is required to apply the ACT. Units used in ACT should be consistent. Choose proper temperatures to effectively analyze the thermodynamic parameters. Abstract: Activated complex theory (ACT), apart from Van 't Hoff equation, has long been applying as an alternative tool to connect the kinetics (reaction rate constant, k ) and thermodynamics parameters (including standard enthalpy of activation, △H ++ ; standard entropy of activation, △S ++ ; standard Gibbs free energy of activation, △G ++ ). The study mainly focuses on ACT application in food systems, especially oil and fruit juice processing. Considering there are several improper calculations or mistakes often found in papers published recently in 2014–2019, three considerations are presented when applying the ACT, including 1) Understand that the reaction should be a single chemical elementary step; 2) Ensure that the units used should be consistent; 3) Effectively analyze the kinetics and thermodynamic parameters by choosing proper temperatures. This study is expected to further improve the understanding and correct application of this well-known theory in future work.